ANALISIS PRAKTIK MINDRING MODERN - Lailyah, Nurzahroh; Yasin, Rozaq Muhammad; Saputri, Pungky Lela (UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This research aims to analyze the practice of Mindring Modern Jaya Mandiri in Kudus from the view of the National Sharia Council (DSN) fatwa of the Indonesian Ulema Council (MUI) No. 110/DSN-MUI/IX/2017 about sale and purchase contracts. This research is a qualitative research with a case study approach. The method used in this research is interview, observation, and documentation. The data validity technique used is triangulation, with analytical procedures including data reduction, data display, making conclusions and verification. The results of this study indicate that the practice of Mindring Modern Jaya Mandiri Kudus is not in accordance with the fatwa of DSN MUI No: 110/DSN-MUI/IX/2017. The use of the lease-purchase contract is not in accordance with the practice of mindring. The appropriate contract is bai’ al-taqsith.